COMPARISON OF FLEXIBLE PAVEMENT THICKNESS DESIGN METHODS - S.W. TANGKUDUNG (NIM 26990002), ELLEN
There are many methods currently available to design a flexible road pavement. Many are empirical , but more recent methods are generally based on structural analysis. Empirical methods include ROAD NOTE 29, AASHTO 1972, AASHTO 1986 and THE ASPHALT INSTITUTE 1972, whereas for structural analytical approaches the SHELL 1978 using BISAR-PC software, and THE ASPHALT INSTITUTE 1983 using the DAMA computer program are two commonly available. A semi-analytical method is the TRRL-LR1132. The BINA MARGA method is based on the AASHTO 1972 with the modification of the Regional Factor in accordance with Indonesian conditions. A comparative analysis between the above methods has been carried out, where the presence of comparable parameters has allowed. A typical specific set of subgrade conditions was chosen, and pavement designs found for a wide range of traffic loading conditions. Where included in the design method environmental conditions have been examined, with particular attention paid to the differences between the AASHTO'72 and AASHTO'86 design procedures. THE ASPHALT INSTITUTE approach is to design for a full-depth asphalt pavement. By application of Layer Coefficients, the result of all designs were converted to a equivalent full-depth situation, in order to compare directly pavement thickness requirement for each of the design methods for a given subgrade and traffic loading conditions. ROAD NOTE 29 and THE ASPHALT INSTITUTE 1970 gave the lowest equivalent full-depth asphalt pavement thickness compared with all the other methods examined. The greatest full-depth equivalent thicknesses were produced with the DAMA program. The specific case of the projected Cikampek-Padalarang toll road has been examined by several methods, taking the data provided by the project consultant. Comment has been made on the given design parameters, in particular the proposed initial traffic conditions and subsequent pavement life loadings, which appear high in light of those recoreded on existing nearby toll roads.